ANALISIS VARIASI V/R GARIS EMISI H? BERDASARKAN PARAMETER FISIS SPEKTRUM PADA BINTANG B- EMISI EW LAC - Shania Bernadi, Ancilla
B-emission (Be) stars are non-supergiant B-type stars whose spectra have, or have had at some time, one or more Balmer lines in emission. Be stars usually have variability on their spectra emission and the variability varies differently on each star. EW Lacertae (HR 8731) is one of B-emission stars which is still studied until now since this star has periodic variability on V/R (violet to red intensity ratio) feature of the emission line. In this thesis, the periode of V/R variability will be determined, as well as the relation with other spectra’s physical parameters of H? lines. Data are downloaded from BeSS (B-Emission Star Spectra) database (http://basebe.obspm.fr/basebe/), from 2001 to 2020. IRAF (Image Reduction and Analysis Facility) program is used for data reduction. The spectra’s parameters calculated are peak velocity ???????? and ????????, radial velocity ????????, FWHM, EW, peak separation 2?????, and absorbtion depth ????????. The results show that the period of V/R long term variation in EW Lac is ±8 years and 4 months. All of the physical parameters show a weak correlation with V/R long term variation. The longterm V/R variation is suspected come from one-armed oscillation in the central equatorial disk of the star.